Effect of Wastewater Discharge From Coffee Processing Plant on River Water Quality, Sidama Region, South Ethiopia - Wubalem Genanaw; Girum Gebremeskel Kanno; Dawit Derese; Mekonnen Birhanie Aregu (SAGE Publishing, 2021)
In Ethiopia, most of the coffee processing plants are generating large amounts of wastewater with high pollutant concentrations and discharge directly into the water bodies untreated or partially treated. The main objective of this study was to assess the effects of coffee wastewater discharged to river water quality using physicochemical parameters and macro-invertebrate indices. This study was conducted from November to the end of December 2019. Ten wastewater and river water samples were taken from coffee the processing plant and river. The macro-invertebrate samples were collected by kick sampling technique using a standard hand net. Shannon and Simpson diversity indices were examined at 3 sampling stations. The Pielou evenness index was also determined. It was found that except for TDS all the parameters of the raw wastewater and river water did not comply with the international discharge limit. The mean concentration of Faro coffee processing plant wastewater were BOD 5 (2409.6 ± 173.1 mg/L), COD (4302 ± 437 mg/L), TSS (2824.6 ± 428.4 mg/L), TDS (3226 ± 623.6 mg/L), and TS (4183.3 ± 432.9 mg/L). Whereas from Bokaso coffee processing plant were BOD 5 (3770 ± 604.4 mg/L), COD (4082.6 ± 921.9 mg/L), TSS (2766 ± 501.7 mg/L), TDS (3017 ± 747.6 mg/L), and TS (3874 ± 471.1 mg/L). A total of 392 macroinvertebrates belonging to 24 families and 7 orders were collected. The benthos assemblage communities in this river were 40, 56, and 296 at downstream 1, downstream 2, and upstream respectively. The value of the Simpson diversity index varies from 0.4 to 0.75. In the same manner, the value of the Shannon diversity index also varied from 0.5 to 1.36. Most of the physicochemical parameters of the raw wastewater were beyond the national and international discharge limits. The quality of Orsha river water downstream was more adversely affected compared to upstream.